TLC for the Detection of Aflatoxin in Groundnut (Arachis hyposaea L.) Kernels - James Jebaseelan Samuel, E.; Durairaj, K.S.P.; Mohan, S. (Asian Journal of Chemistry, 2010)
Cash crops such as groundnut, cashew, cotton, sesame, sugarcane, tobacco, turmeric and banana play vital role in the growth of economic and nutritional status in India. Of these, groundnuts (Arachis hyposaea L.) is the most important major crops, which is energy rich and micro nutrient contents are relatively high compared with other corps. Out of total production, 12% is used as seeds, 8% for edible purpose, 70% extraction of oils and 10% for export and hence it is considered to be an economically important crop. This crop is found to be attacked by number of fungal diseases. Besides these fungal diseases groundnut is found to be affected by "Aflatoxins". They are probably the most serious fungal disease of groundnut on a worldwide scale. Aflatoxins are a group of highly oxygenated heterocyclic compounds with closely related structure of B1, B2, G1 and G2. These aflatoxins are closely related group of secondary fungal metabolites which have been epidemiologically implicated carcinogens in human being. The carcinogenic properties of aflatoxin have reinforced the concept that naturally occurring mycotoxins may be involved in the etiology of human cancer on a broad basis. Aflatoxin producing fungi are widely distributed in tropical and subtropical areas. Groundnut is highly susceptible to aflatoxin contamination. An attempt has been made to determine the possible variations in the amount of aflatoxin-B, present in the groundnuts grown in two different fields treated with chemical fertilizers and organic manure alone independently.